Princípio fundamental da contagem no Ensino fundamental: uma abordagem partindo do concreto para o abstrato. - Barros, Edgar Pereira (2020)
To approach the teaching of the Fundamental Principle of Counting (FPC) with elementary school students final years: a pedagogical practice starting from the use of concrete material to later work more complex and abstract problems. The objective is to show that using concrete can be a resource to motivate students and improve mathematics teaching, specifically of the Fundamental Principle of Counting. The hypothesis to be proved is that this practice makes classes more interesting, showing students the importance of mathematics in the classroom and in practical life. The purpose of this paper is to encourage the use of real things to teach the Fundamental Principle of Counting, thus motivating the students to understand and solve problems related to this theme, from the simplest to the most complex and abstract.